DYNAMICS OF EARLY MARRIAGE AND ITS IMPLICATIONS FOR HOUSEHOLD QUALITY OF LIFE FROM THE PERSPECTIVE OF SUSTAINABLE DEVELOPMENT GOALS (SDGs) ACHIEVEMENT IN SAMBIREJO TIMUR VILLAGE, PERCUT SEI TUAN DISTRICT - Aprilia Rahmatunisa Purba; Nuriza Dora (SOSIOEDUKASI, 2026)
Early marriage remains a significant social issue in Indonesia, affecting household quality of life and the achievement of the Sustainable Development Goals (SDGs). This study aims to analyze the dynamics of early marriage and its implications for household quality of life from the perspective of SDGs in Sambirejo Timur Village, Percut Sei Tuan District. This study employed a qualitative descriptive approach. Thirteen informants were selected through purposive sampling, including the neighborhood head, young married couples, and community members. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings indicate that early marriage is influenced by economic hardship, low educational attainment, social environment, and community norms that continue to tolerate the practice. Young couples experienced various challenges, including unstable economic conditions, marital adjustment, child-rearing responsibilities, and psychological pressure associated with assuming family roles at an early age. Despite these challenges, family support, effective communication, and mutual cooperation helped strengthen household resilience. The study also reveals that early marriage affects the achievement of several SDGs, particularly No Poverty, Good Health and Well-being, Quality Education, Gender Equality, Decent Work and Economic Growth, and Reduced Inequalities. Strengthening education, family economic empowerment, reproductive health education, premarital counseling, and family resilience programs is essential to reducing early marriage and supporting sustainable development at the local level